Rapidly Varying Ionization Features in a Quasi-periodic Eruption: A Homologous Expansion Model for the Spectroscopic Evolution - Joheen Chakraborty; Peter Kosec; Erin Kara; Giovanni Miniutti; Riccardo Arcodia; Ehud Behar; Margherita Giustini; Lorena Hernández-García; Megan Masterson; Erwan Quintin; Claudio Ricci; Paula Sánchez-Sáez (The Astrophysical Journal)
Quasi-periodic eruptions (QPEs) are recurring bursts of soft X-ray emission from supermassive black holes, which a growing class of models explains via extreme mass ratio inspirals (EMRIs). QPEs exhibit blackbody-like emission with significant temperature evolution, but the minimal information content of their almost pure-thermal spectra has limited physical constraints. Here we study the recently discovered QPEs in ZTF19acnskyy (“Ansky”), which show absorption-like features evolving dramatically within eruptions and correlating strongly with continuum temperature and luminosity, further probing the conditions underlying the emission surface. The absorption features are well described by dense ionized plasma of column density N _H ≳ 10 ^21 cm ^−2 , blueshift 0.06 ≲ v / c ≲ 0.4, and either collisional or photoionization equilibrium. With high-resolution spectra, we also detect ionized blueshifted emission lines suggesting a nitrogen overabundance of $21.{7}_{-11.0}^{+18.5}× $ solar. We interpret our results with orbiter–disk collisions in an EMRI system, in which each impact drives a shock that locally heats the disk and expels X-ray-emitting debris undergoing radiation-pressure-driven homologous expansion. We explore an analytical toy model that links the rapid change in absorption lines to the evolution of the ionization parameter and the photosphere radius, and we suggest that ∼10 ^−3 M _⊙ ejected per eruption with expansion velocities up to ${v}_{{\rm{\max }}}\sim 0.15c$ can reproduce the absorption features. With these assumptions, we show that a P Cygni profile in a spherical expansion geometry qualitatively matches the observed line profiles. Our work takes a first step toward extending existing physical models for QPEs to address their implications for spectral line formation.